The role of mitochondria-related genes and immune infiltration in carotid atherosclerosis: identification of hub targets through bioinformatics and machine learning approaches - Liu, Dan; Guo, Kun; Li, Min; Yu, Xiaochen; Guan, Xue; Guan, Xiuru (Frontiers in Genetics, 2025)
ObjectiveAtherosclerosis (AS) is the underlying pathology of atherosclerotic cardiovascular disease and a major cause of cardiovascular-related mortality. Chronic inflammation and mitochondrial dysfunction, triggered by the infiltration of various immune cells, are key factors in the progression of AS. However, the interaction and crosstalk between these factors remain unclear.MethodsTwo gene expression datasets, GSE100927 and GSE43292, were downloaded from the National Center for Biotechnology Information Gene Expression Omnibus (NCBI GEO) database, covering carotid atherosclerosis and control groups. After identifying the common differentially expressed genes (DEGs), mitochondria-related DEGs (Mito-DEGs) were obtained through Weighted Gene Co-expression Network Analysis (WGCNA) and machine learning approaches. Immune infiltration analysis and comparison were subsequently performed. The single-cell dataset GSE159677 further validated the expression proportions of relevant genes in different cell populations during the progression of AS. Additionally, cell-cell communication and trajectory analysis within the immune landscape were utilized to infer the pathways of cell state transitions within AS clusters. THP-1 cells were cultured in vitro, and the foam cell model was established by the addition of oxidized low-density lipoprotein (ox-LDL). The expression trends of hub Mito-DEGs were confirmed via qRT-PCR.ResultsFrom the GSE100927 and GSE43292 datasets and the MitoCarta3.0 database, three hub Mito-DEGs closely associated with AS were ultimately identified: CASP8, GATM, and LAP3. Subsequent comprehensive bioinformatics analysis of these hub genes further emphasized the importance of the immune system in AS. Immune profiling based on the CIBERSORT algorithm revealed significantly increased infiltration of activated mast cells, monocytes, memory B cells, T follicular helper cells, and M0 macrophages in the immune microenvironment of AS. Single-cell analysis showed that GATM and LAP3 were enriched in monocytes and macrophages, while CASP8 exhibited increased expression in NK cells, T cells, and monocytes. In addition, in vitro cell experiments demonstrated that mRNA expression levels of the hub Mito-DEGs were significantly elevated in the lipid-laden foam cell group compared to the control group, consistent with the expression patterns observed in the single-cell dataset.ConclusionThis study revealed the interaction between Mito-DEGs and the immune system in AS. These findings may provide new insights into therapeutic monitoring and prognosis evaluation.